Small molecule based fluorescent chemosensors for imaging the microenvironment within specific cellular regions. (22nd September 2021) - Yin, Junling; Huang, Ling; Wu, Luling; Li, Jiangfeng; James, Tony D.; Lin, Weiying
Abstract : This review comprehensively summarizes and highlights recent progresses in the design and application of small molecule based fluorescent probes for sensing and imaging the microenvironment within specific cellular regions since 2015. Abstract : The microenvironment (local environment), including viscosity, temperature, polarity, hypoxia, and acidic-basic status (pH), plays indispensable roles in cellular processes. Significantly, organelles require an appropriate microenvironment to perform their specific physiological functions, and disruption of the microenvironmental homeostasis could lead to malfunctions of organelles, resulting in disorder and disease development. Consequently, monitoring the microenvironment within specific organelles is vital to understand organelle-related physiopathology. Over the past few years, many fluorescent probes have been developed to help reveal variations in the microenvironment within specific cellular regions. Given that a comprehensive understanding of the microenvironment in a particular cellular region is of great significance for further exploration of life events, a thorough summary of this topic is urgently required. However, there has not been a comprehensive and critical review published recently on small-molecule fluorescent chemosensors for the cellular microenvironment. With this review, we summarize the recent progress since 2015 towards small-molecule based fluorescent probes for imaging the microenvironment within specific cellular regions, including the mitochondria, lysosomes, lipid drops, endoplasmic reticulum, golgi, nucleus, cytoplasmic matrix and cell membrane. Further classifications at the suborganelle level, according to detection of microenvironmental factors by probes, including polarity, viscosity, temperature, pH and hypoxia, are presented. Notably, in each category, design principles, chemical synthesis, recognition mechanism, fluorescent signals, and bio-imaging applications are summarized and compared. In addition, the limitations of the current microenvironment-sensitive probes are analyzed and the prospects for future developments are outlined. In a nutshell, this review comprehensively summarizes and highlights recent progress towards small molecule based fluorescent probes for sensing and imaging the microenvironment within specific cellular regions since 2015. We anticipate that this summary will facilitate a deeper understanding of the topic and encourage research directed towards the development of probes for the detection of cellular microenvironments.